Adverse Effects of Subchronic Dose of Aspirin on Reproductive Profile of Male Rats. (12th April 2016) - Vyas, Archana; Ram, Heera; Purohit, Ashok; Jatwa, Rameshwar
Abstract : Aspirin (acetylsalicylic acid) is widely used for cardiovascular prophylaxis and as anti-inflammatory pharmaceutical. An investigation was carried out to evaluate the influence of subchronic dose of aspirin on reproductive profile of male rats, if any. Experimental animals were divided into three groups: control and aspirin subchronic dose of 12.5 mg/kg for 30 days and 60 days, respectively, while alterations in sperm dynamics, testicular histopathological and planimetric investigations, body and organs weights, lipid profiles, and hematology were performed as per aimed objectives. Subchronic dose of aspirin reduced sperm density, count, and mobility in cauda epididymis and testis; histopathology and developing primary spermatogonial cells (primary spermatogonia, secondary spermatogonia, and mature spermatocyte) count were also significantly decreased in rats. Hematological investigations revealed hemopoietic abnormalities in 60-day-treated animals along with dysfunctions in hepatic and renal functions. The findings of the present study revealed that administration with subchronic dose of aspirin to male rats resulted in altered reproductive profiles and serum biochemistry.